Development of National University Asset Management Application Using the Android-Based Life Cycle Development System Method - Ryan maulana; Septi Andryana; Aris Gunaryat (Institute of Computer Science (IOCS), 2020)
The goal of developing an asset management system is expected to make it easier for users to manage assets. The results of the application development that is developed first is the admin login if it is logged in, will enter the home menu, then the admin adds assets in the added assets menu according to the user's needs, if the assets have been added, appears in the asset view menu, all available asset data can be seen in the asset view menu, if the user requests an asset there is a request to request an asset, then requests as an admin to accept the request for the asset the user needs, if it has been received by Asset admin will appear in the history menu.